Solving the independent Set problem by using tissue-like P systems with cell division - Daniel Díaz-Pernil; Miguel A. Gutiérrez-Naranjo; Mario J. Pérez-Jiménez; Agustín Riscos-Núñez (Springer Berlin / Heidelberg, 2009)
Tissue-like P systems with cell division is a computing model in the framework of Membrane Computing inspired by the intercellular communication and neuronal synaptics. It considers the cells as unit processors and the computation is performed by the parallel application of given rules. Division rules allow an increase of the number of cells during the computation. We present a polynomial-time solution for the Independent Set problem via a uniform family of such systems.
A Homage to Professor Mira’s Scientific Legacy. Lecture Notes on Computer Science